APPROPRIATE PLANTING TIME FOR PROFITABLE PRODUCTION OF QUALITY SEED OF KENAF (Hibiscus canabinus L.) IN SOUTH WESTERN NIGERIA - Adetumbi, Adedayo Johnson; Ogunniyan , Dotun; Ajijola, Sikiru; Oyegbami, Ajoke; Adeniyan , Nicholas (Journal of Agricultural Sciences (Belgrade), 2022)
Low seed yield realized from kenaf production in different agro-ecologies in south western Nigeria has been partly attributed to effect of climate change. An experiment was therefore, conducted to validate information on the response of kenaf to prevailing weather condition and determine the most appropriate planting time to produce optimum seed yield of acceptable quality that will be profitable in humid agro-ecologies of Nigeria. The study was conducted at five research stations (Ibadan, Ilora, Ikenne, Orin Ekiti and Kishi) of the Institute of Agricultural Research and Training (I.A.R.&T) Ibadan Nigeria in 2018 and 2019 planting season.  Five varieties of kenaf (Cuba108, Ifeken DI 400, Ifeken100, Ifeken 400 and Tianung-2) were planted in monthly interval from June to August of each year in randomized complete block design (RCBD) with three replicates. Harvesting, threshing and cleaning were manually done, after which samples of clean seeds were analyzed for seed quality. Data were obtained on Plant height at harvest, seed yield related traits and seed quality parameters. Profitability analysis was also conducted to estimate the cost and returns to production in the different locations. Kenaf seed yield and quality is highly influenced by the production environment. It is concluded that planting of kenaf in mid-June in South Western Nigeria will give optimum seed yield of high quality with profitable gross return on investment.
Keywords: Kenaf, planting time, quality seed, South Western Nigeria